2020
DOI: 10.1002/pol.20190194
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic water soluble cationic ring opening metathesis copolymer as an antibacterial agent

Abstract: Bacterial infection is a global problem, especially resistance acquired by bacteria against to antibiotics; there is urgent need for the development of antibiotics. Here, we proposed dendron‐grafted polymers via ring opening metathesis polymerization (ROMP) featuring different with tailored hydrophobicity/hydrophilicity and cationic charges. Dendritic oxanorbornene derivatives were synthesized having two and six carbon linkers and their corresponding random and block copolymers were prepared having pendant pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 90 publications
0
13
0
Order By: Relevance
“…PAMAM G2 characterized according to the literature 27 . Shortly, FT‐IR spectra indicated that (data not shown), NH 2 peak of EDA at 3368 and 3284 cm −1 completely vanished after methyl acrylate Michael addition by appearing a new esteric carbonyl peak at 1731 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…PAMAM G2 characterized according to the literature 27 . Shortly, FT‐IR spectra indicated that (data not shown), NH 2 peak of EDA at 3368 and 3284 cm −1 completely vanished after methyl acrylate Michael addition by appearing a new esteric carbonyl peak at 1731 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Presence of acrylamide repeating units might cause the swelling of Bare GEL 27 . Incorporation of amine functional group dendrimer (GEL G2‐1‐1) increased water adsorption to 427%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, zeta potential (ζ-potential) measurements were made by the dynamic light scattering (DLS) method to investigate the interaction between negatively charged bacterial membranes and cationic polymers to speculate about the mode of action of antimicrobial polymers. 29,34 First, we performed zeta potential and size values of the polymers in buffer to observe the formation of aggregate polymer itself to elucidate the relationship between polymer aggregation and antibacterial activity (Figure 3; for detailed information, see Table S3 and the graph in Figure S30). When 4c_10k, which has the lower activity against S. aureus (MIC =32 μg mL −1 ), was examined, it was seen that the zeta potential value was the highest (11 ± 0.63 mV) among the homopolymer series (Figure 3).…”
Section: Measurement Of Bacterial and Polymer Interactions Withmentioning
confidence: 99%